"Embracing diversity in all its forms": The voluntary secondary sector in Irish education - Eamonn Carroll; Selina MacCoy; Keyu Ye (The Economic and Social Research Institute (ESRI), 2024)
The Irish education system is undergoing significant change as it navigates the challenges of the 2020s. Schools are at the frontline of Ireland's efforts to integrate migrant families, build an inclusive society and tackle generational socioeconomic inequality. They are also, increasingly, key sites of contestation over deep social questions like the place of faith and secularism in public institutions and the best path to ensuring young people thrive, regardless of their gender or sexual orientation. While many of these challenges resonate across the second-level sector as all schools grapple with the difficulties and opportunities of educating young adults in today's Ireland, the focus of this report is on the voluntary secondary school sector. The report presents rich evidence from a mixed-method research study across 21 voluntary secondary schools. The research was commissioned by the Joint Managerial Body for Voluntary Secondary Schools (JMB), with the research questions designed to examine the features and experiences of students, teachers and school leaders across the voluntary sector. However, the study allows for comparisons between experiences in voluntary secondary schools and other sectors. In particular, the survey of students undertaken in this study is compared to the nationally representative longitudinal study Growing Up in Ireland (GUI) and the International Student Assessment (PISA study) on 15 year olds in Ireland and across the European Union (EU). This approach allows for a deep exploration of the voluntary secondary sector, while also placing experiences in a national and international context.
Keywords: 330